The Meaning of Minangkabau Verb ‘Mangecek’: A Natural Semantic Metalanguage Analysis - Ridella, Natasya; Jufrizal, Jufrizal (English Language and Literature, 2024)
This study aimed to analyze words in Minangkabau that have the same semantic prime: ‘mangecek’ using Natural Semantic Metalanguage (NSM). This research was conducted using a descriptive qualitative approach. This research used a theory by Goddard and Wierzbicka about NSM. The data found in this study were connected words that are associated with the prima semantic ‘say’/’mangecek’ in Minangkabau language. The sources of this data were the 10 informants who native speakers from Padang city, which is the capital city of the West Sumatera province. The data were collected using interview guidelines, recording equipment, and writing equipment. An interactive model of data analysis is used to analyze the data. From the data that were collected and analyzed there are a total of 10 words related to the semantic prime of ‘Say’: maupek, bacaruik, malawan, mangaluah, manyindia, marayu, bagunjiang, manyabuik, mamuji, and manyapo. These words are similar but not exactly the same so it will create misunderstanding in the diction.